What we have lost: Mastitis resistance in Holstein Friesians and in a local cattle breed. (February 2018) - Curone, Giulio; Filipe, Joel; Cremonesi, Paola; Trevisi, Erminio; Amadori, Massimo; Pollera, Claudia; Castiglioni, Bianca; Turin, Lauretta; Tedde, Vittorio; Vigo, Daniele; Moroni, Paolo; Minuti, Andrea; et al.
Abstract: In Holstein Friesian dairy cows, selective pressure for increased milk production has led to a higher propensity to disease, including mastitis, when compared to less selected and lower producing dairy breeds. The biology underpinning the higher resistance to disease of such "local breeds" is not fully understood. With the aim of investigating the factors associated to this phenomenon, we applied a multidisciplinary approach to compare innate immune response patterns, metabolic parameters, milk protein profiles and the milk microbiota in Holstein Friesian and Rendena cows reared in the same farm and under the same management conditions. Quarter milk samples and blood plasma were collected from all cows at dry-off, 1 day after calving, 7–10 days after calving and 30 days after calving. Quarter milk samples were subjected to bacteriological culture, characterization of the milk microbiota by 16S metagenomics, milk protein profiling by electrophoresis and densitometry, somatic cell counting, measurement of the inflammation marker cathelicidin and assessment of different innate immune-related mediators such as lysozyme, CD45, IL-1β, TNF-α, PTX3, IL-1R8. In parallel, the main inflammometabolic parameters were measured in blood plasma samples. Despite having relatively few animals (6 moderate-yielding Holstein Friesian and 4 low-yielding Rendena) some important differences were apparent. Holstein Friesian cows showed a more severe fat mobilization and systemic inflammatory response postpartum in comparison with Rendena cows, which had a greater postpartum muscle mass and an increased amino acid mobilization compared to Holstein Friesians. Upon bacteriological analysis, contagious bacteria such as Staphylococcus aureus and Streptococcus agalactiae were absent, but significant differences were seen in the general composition of the milk microbiota of the two breeds. Concerning the milk protein abundance profile, pronounced differences were seen in colostrum, with significantly higher amounts of immunoglobulins and other immune-related proteins in Rendena. Added to this, the expression of innate immune related genes such as PTX-3, IL-1β, TNF-α, and KRT5 expression in milk epithelial and leukocyte cell components, respectively, was lower in Holstein Friesian colostrum compared with Rendena. In conclusion, several differences were observed in the two breeds, in spite of the same farming conditions. The observations reported in this work present numerous pointers to the factors that may provide autochthonous, more rustic breeds with a higher resistance to disease. Highlights: Holstein Friesian and Rendena cows have different metabolic traits. Mastitis markers are higher in Holstein Friesian milk. The microbiota biodiversity is lower in Rendena milk. The colostrum protein profile is markedly different in the two breeds. Mammary innate immune response patterns display breed-specific differences.